HUBUNGAN PERAN AYAH DALAM PENGASUHAN DENGAN KEPERCAYAAN DIRI ANAK USIA 5-6 TAHUN DI PAUD CENDANA RUMBAI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Nuri Sulistiyani; Daviq Chairilsyah; Zulkifli N Zulkifli N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is to know the The correlation between fathers' role in parenting with the self confidence of the children aged 5-6 years old in Cendana Rumbai EarlyChilhood in Rumbai Pesisir Pekanbaru. The population of this reserach are the all of children aged 5-6 years old in earlychildhood Cendana Rumbai in Rumbai Pesisir Pekanbaru that amounting 30 people, and the total of the sample is 30 people. The method that is used in this research is correlation technique Person Product Moment to see the correlation between fathers’ role in parenting with the self confidence of the children. The data collection technique used interview and observation in scale likert, statictical method analysis with SPSS for windows Ver. 23. Based on the result of hypothesis testing there is a significant positive correlation between the role of fathers in parenting with the self confidence of the children aged 5-6 years old in Earlychildhood cendana rumbai in Rumbai pesisir pekanbaru. This can be seen by the correlation coeffition value of rxy = 0.670 and the significance level of 0.000 < 0.05. The level of the correlation between the fathers' role in parenting with the self confidence of the children aged 5-6 years old in earlychildhood Cendana Rumbai in rumbai pesisir pekanbaru is included in a high category with a proven coefficient determinan of 38,%, means that the fathers' role in parenting has an effect of 38.7% on children's self confidence.Key Words: The fathers' role, the self confidence of the children